Fungsi Register Urban Mama dalam Grup Aimi dan HHBF (Kajian Sosiolinguistik) - ARTIFA SORRAYA; Tities Hijratur Rahmah (IKIP Budi Utomo Malang, 2022)
Register is a variation of language that is adapted to the context of language use. This study is a study of urban mama registers in the AIMI and HHBF Facebook groups that are studied with sociolinguistics. The research aims to find several things, namely the register function. The researcher uses a qualitative approach with descriptive analysis. The study uses three methods, namely data collection methods, data analysis, and presentation of data analysis. Data collection using the method of listening and note related to the use of urban mom language in conversations in the AIMI group (Association of Indonesian Breastfeeding Mothers) and HHBF (HeathlyHommade Baby Food), data collection was also carried out by in-depth interviews and FGD. Data analysis uses register analysis, which is analyzing the specific vocabulary used in certain jobs or communities. The method of presenting the results of data analysis is an informal method that is using words that are easily understood. The results showed that the urban mama register function in the AIMI and HHBF groups was 1) emotive function, 2) conative function, 3) referential function, 4) fatigue function, and 5) metalingual function.